Can HIV treatments inform other contexts? A trial of an additional indication for co-trimoxazole prophylaxis. - Ngari, M; Thitiri, J; Mwalekwa, L; Fegan, G; Berkley, J (BMJ Publishing Group, 2017)
Co-trimoxazole prophylaxis is part of HIV management of opportunistic infections. However, it is not known if co-trimoxazole prophylaxis can prevent opportunistic infections among other vulnerable population such as people with complicated severe acute malnutrition (SAM). It is unclear if and how nutritional recovery may reduce susceptibility to infectious diseases like pneumonia with co-trimoxazole prophylaxis. We share secondary analysis results of multicentre, double-blinded, randomised clinical trial (ClinicalTrials. gov, number NCT00934492) of daily co-trimoxazole prophylaxis among HIV non-infected children with SAM in Kenya.